HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KELENTURAN OTOT PUNGGUNG DENGAN HASIL TOLAK PELURU PADA SISWA PUTRA KELAS XI SMK N 7 PEKANBARU - Arif Gunawan; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: According to the previous statement and the result of the research observation into the male students of XI grade at SMK N 7 Pekanbaru, the result of the male students’ shot put was not maximal. It could be observed from the students’ shot which did not reach the learning standard. The aim of the research was to see the relationship of shoulder arm muscle power and back muscle flexibility with the result of shot put for the male students of XI grade at SMK N 7 Pekanbaru. The population was XI grade SMK N 7 Pekanbaru consisting of 20 male students. The research used total sampling. It means that all population of male students as the samples with the amount of 20. The instruments were shoulder arm muscle power test by using expanding dynamometer test, back muscle flexibility test by using sit and reach test, and shot put test by using the shot put result.The data was analysed by using simple and multiplied product moment correlation. Based on the research result, it was obtained that the power of shoulder and arm muscle had a relationship with the result of the male students’ shot put of XI grade SMK N 7 Pekanbaru. From the result, it was obtained that back muscle flexibility had a relationship with the result of shot put for the male students of XI grade at SMK N 7 Pekanbaru. There was a significant result between the power of shoulder arm muscle and the flexibility of back muscle through the result of the male students’ shot put in XI grade at SMK N 7 Pekanbaru.Keywords: soulder arm muscle power, back muscle flexibility, the result of shot put